Human-centric approach to creating sustainable innovation in the context of Industry 5.0 - Agnieszka Bieńkowska; Katarzyna Tworek; Olga Voropai; Joanna Zimmer (Entrepreneurial Business and Economics Review (EBER), 2025)
Objective: The article aims to explore how human-centric organisational practices, combined with employee dynamic capabilities (EDC), can drive sustainable innovation in the Industry 5.0 concept. Research Design & Methods: We conducted an empirical study to verify hypotheses regarding human-centric organisational practices and their impact on sustainable innovation. We conducted a questionnaire-based study among 462 organisations from Poland. We tested research hypotheses with a linear regression analysis with a mediator using the Macro Process for IBM SPSS. Findings: The critical literature review and empirical verification of the proposed hypotheses indicated that human-centric organisational practices influence sustainable innovation through EDC. Organisational employees are not mere resources but dynamic change agents who, supported by appropriate practices, drive innovation among organisations exhibiting characteristics of the Industry 5.0 concept. Human-centric organisational practices enable EDC, allowing organisations to benefit from them because of the strengthened ability to generate sustainable innovations. Implications & Recommendations: Organisations seeking to implement sustainable innovation should adopt a more dynamic and human-centric approach to human resource management, prioritizing practices that enhance EDC such as adaptability, critical thinking, and creativity. The results confirm that achieving sustainability through innovation requires investments that go beyond technology and infrastructure. Future research could focus on different geographical or cultural contexts. Moreover, scholars could analyse in detail specific employee-centric practices and their impact on EDC and sustainable innovation and extend the proposed model to include new concepts. Contribution & Value Added: The study's results extend the resource-based view and the dynamic capabilities framework by demonstrating that human-centric organisational practices are critical in enhancing EDC for fostering innovations among organisations exhibiting characteristics of the Industry 5.0 concept. They also contribute to the sustainable innovation literature by showing that sustainable innovation is not solely a product of top-down initiatives or rely mainly on technological advancements but also critically depends on the dynamic capabilities of employees that are supported by human-centric organisational practices. Leaders pursuing sustainability through innovation should focus on investing in human-centric practices, particularly those related to the enhancement of EDC.
Keywords: M54; O31; Q56; 330; employee dynamic capabilities; human-centric organisational practices; Industry 5.0; sustainable innovation; technology